RANCANG BANGUN SISTEM INFORMASI STOK OBAT PADA APOTEK ARICK BERIZIN KABUPATEN BATANG HARI - Suana, Irma; Romadi, Agung; -, Mulyadi (JURNAL AKADEMIKA, 2023)
The author took the initiative to build an application that can help manage pharmacy drug stock data to make it more effective and efficient which will be built with the Visual Basic NET programming language. This thesis uses a qualitative descriptive approach with data collection methods through observation, interviews and documentation. Based on the research obtained, the following conclusions are obtained: building a collaboration in the IT sector that is able to make it easier to process drug stock data at licensed Arick pharmacies in the form of Visual Basic.NET. With the information system at the Licensed Arick Pharmacy, this can provide convenience and minimize errors in processing drug inventory data and creating a better working system.